European Academy of Allergy and Clinical Immunology position paper on endoscopic scoring of nasal polyposis. Issue 4 (3rd February 2023) - Gevaert, Philippe; De Craemer, Jarno; Bachert, Claus; Blauwblomme, Manon; Chaker, Adam; Cingi, Cemal; Hellings, Peter W.; Hopkins, Claire; Hox, Valérie; Fokkens, Wytske J.; Klimek, Ludger; Lund, Valerie; et al.
Abstract: Nasal endoscopy is not only used for the diagnosis of chronic rhinosinusitis with nasal polyps (CRSwNP), but also for monitoring the response to therapy playing an important role in both daily practice and research. In contrast to patient‐reported outcomes, endoscopic nasal polyp scoring by independent blinded readers is an objective measurement, not influenced by the placebo effect. It is safer and cheaper compared with computed tomography imaging and therefore, better suited for regular assessments of the extent of the disease. Since the early 90s, a variety of endoscopic staging methods have been proposed and used in clinical research, making it hard to compare results from different studies. This paper resulted from a task force with experts in the field of CRSwNP, originated by the Ear, Nose and Throat section of the European Academy of Allergy and Clinical Immunology and aims to provide a unified endoscopic NP scoring system that can serve as a reference standard for researchers, but also as a useful tool for practitioners involved in the management of CRSwNP. Abstract :